Slovenia: In Search of a Sensitive Balance Between Economic, Social, and Ecological Functions of Agricultural Land and Rural Areas - Avsec, Franci (Acquisition of Agricultural Lands, 2022)
The Slovenian Constitution guarantees the right to private property and inheritance; emphasizes the economic, social, and environmental functions of property and grants special protection to agricultural land. According to these provisions, middle-sized family farms are protected against division so that they are, in principle, inherited by a single testamentary or intestate heir, while the number of other heirs and their inheritance shares are reduced. The legal transfer of agricultural land, forests, and farms is subject to several substantial restrictions and prior administrative control. After a general prohibition to divide the protected farms inter vivos was lifted in spring 2022, the disposal of protected farms has been less restricted, but the number of protected farms is expected to decrease. The legislation on agricultural land, protected farms, forests, and agricultural communities, as well as on nature conservation, water, cultural heritage protection, and spatial planning, regulate several preemption rights, of which two or more concur in many a case. To prevent the circumvention of statutory preemption rights, conclusion donation contracts are also restricted. In certain cases, the physical division of agricultural and forest plots is prohibited by the law. Lease contracts of agricultural land are also regulated by some special provisions (relating to prelease rights, minimum lease period, and so on) and subject to prior administrative control. The current legislation and international treaties allow citizens and legal persons of certain states (e.g., the EU member states) as well as persons with the status of a Slovene without Slovene citizenship to acquire agricultural land, so that reciprocity is not required. Citizens and legal persons of certain other states may acquire agricultural land based on a legal transaction, inheritance, or a state body’s decision under condition of reciprocity, while citizens and legal persons of all other states may acquire agricultural land only on the basis of inheritance and under a condition of reciprocity. The statutory provisions on the legal transfer of agricultural land and holdings have been assessed several times by the Constitutional Court from the standpoint of constitutional right to private property and inheritance; economic, social, and environmental function of property; free economic initiative; rule of law; and the principles of legal certainty and proportionality. Keywords: agricultural land, farms, legal transfer, Slovenia